Teknik Menjadi Pembawa Acara dalam Konteks dan Setting Acara Formal - Akh Ubaidillah; Mad Sa’i; Masti Yanto (Indo Publishing, 2025)
In the world of broadcasting, business meetings, or formal events, the role of the MC is very important to maintain the smooth running of the event and create an atmosphere that is appropriate to the formal context. However, being an MC in a formal setting requires more than just public speaking skills; it requires special techniques that involve mastery of the material, emotional regulation, effective communication, and adaptation to certain situations. This study aims to identify the main techniques that can be used by an MC in presenting a formal event professionally and effectively. The research method used is a qualitative approach with literature studies and in-depth interviews with seven professional MCs who have had at least five years of experience in filling formal events. The results of the study indicate that the success of an MC in a formal event depends on thorough preparation, self-control, improvisation skills, and the ability to build relationships with the audience even within formal boundaries. These findings provide practical contributions for individuals and organizations in improving the quality of formal event management through the strategic role of an MC.